2017
DOI: 10.1161/strokeaha.116.013620
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale and Cryptogenic Strokes in the Stroke in Young Fabry Patients Study

Abstract: T he relevance of a patent foramen ovale (PFO) as a frequent cause of stroke is controversial. [1][2][3][4] Because of its higher prevalence, it is generally considered causative in cryptogenic stroke patients aged <55 years. 5,6 However, the term cryptogenic stroke itself is not well defined and comprises typically also patients with less distinctive diseases like Background and Purpose-A patent foramen ovale (PFO) is disproportionately prevalent in patients with cryptogenic stroke. Without alternative explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Due to the lower prevalence of classical vascular risk factors, the etiology of juvenile stroke has a different focus compared to stroke etiology in older patients. Besides coagulation, disorders, CNS vasculitis, dissection, and genetic disorders such as Fabry's disease are increasingly important ( 21 , 22 ). However, no Fabry's disease was detected among 176 patients who received specific tests in our study and apart from dissection, other specific stroke etiologies were rarely identified in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lower prevalence of classical vascular risk factors, the etiology of juvenile stroke has a different focus compared to stroke etiology in older patients. Besides coagulation, disorders, CNS vasculitis, dissection, and genetic disorders such as Fabry's disease are increasingly important ( 21 , 22 ). However, no Fabry's disease was detected among 176 patients who received specific tests in our study and apart from dissection, other specific stroke etiologies were rarely identified in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanied by the natural deterioration of cognitive function due to aging, elder people are more prone to depression and cognitive impairment following stroke. Depression and cognitive impairment affect about 30–50% stroke survivors, respectively (Towfighi et al, 2016 ). Therefore, it is critical and pressing to understand the patterns and underlying mechanisms of cognition in relation to geriatric depression in the context of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Depression deteriorates recovery in mental status and cognitive performance, as there is an approximately 30% difference in the improvement rate of depressed patients and non-depressed patients (Morris et al, 1992 ). Domains of mental status, such as speech disturbance and impaired consciousness, contribute to and further help predict the development of PSD (Towfighi et al, 2016 ). Poorer cognitive performance in other non-memory domains, such as executive function, visuospatial ability, and attention, was also observed in those who had higher GDS scores (Tene et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, the presence of other risk factors cannot be used as evidence to exclude the pathogenesis of PFO. Huber et al [7] demonstrated that after adjusting for age factors, for patients suffering from cryptogenic stroke without vascular risk factors, such as hypertension and diabetes mellitus, the detection rate of PFO was 36%, while the detection rate of PFO in patients with vascular risk factors was 20%. The study speculated that PFO-AS was likely to affect posterior circulation, which might be related to the higher blood flow velocity of posterior circulation than that of anterior circulation during Valsalva action.…”
Section: Discussionmentioning
confidence: 99%